Pengaruh Disiplin Kerja, Literasi Digital, dan Motivasi Kerja Terhadap Kinerja Pegawai UPTD BBI TP Alsintan Lampung - Liza Karmela; Winda Rika Lestari (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study analyzes the effect of work discipline, digital literacy, and work motivation on employee performance at the UPTD Balai Benih Induk Tanaman Pangan dan Alat Mesin Pertanian (Alsintan) in Lampung Province. The research used a quantitative descriptive approach with 35 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through multiple linear regression, supported by tests of normality, linearity, multicollinearity, determination coefficient, t-test, and F-test. The findings show that work discipline has a positive and significant effect on employee performance, indicating that better adherence to rules, punctuality, and responsibility leads to improved performance. Digital literacy also has a positive and significant effect, meaning that stronger ability to use digital technology and information in work contributes to better performance. Work motivation likewise has a positive and significant effect, showing that higher internal and external drive improves work spirit and quality. In addition, work discipline, digital literacy, and work motivation simultaneously have a significant effect on employee performance. These results suggest that employee performance can be improved through integrated efforts to strengthen discipline, enhance digital literacy, and maintain motivation in the workplace.